PENGUATAN KEPAHAMAN NILAI TOLERANSI DAN KERUKUNAN ANTAR UMAT BERAGAMA MELALUI KAMPUNG MODERASI BERAGAMA (KMB) SIBOLGA SELATAN - Darania Anisa; Erna Ikawati (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
Community Service Based on Religious Moderation is carried out as a tolerant attitude, an embodiment of religious moderation which is actualized through the Religious Moderation Village (KMB), carrying out dialogue between religious believers as a form of harmony and tolerance. As well as literacy materials to minimize conflict between religious communities. South Sibolga has a diverse population, 67.15% Muslim, 29.23% Protestant, 3.04% Catholic and 0.65% Buddhist. This service uses the Participatory Action Research (PAR) method including planning, implementation and discovery of field facts. The results of the Service show an increase in the understanding of religious moderation in the South Sibolga community from 55% to *)% based on the results of questionnaire data that was distributed before and after the activity was carried out.